Chaos-based Pseudo-Random Number Generators and Chip Implementation - Li, Zhong; Li, Ping; Mao, Yaobin; Halang, W.A. (IFAC Proceedings Volumes, 2005)
Cryptography as an ancient subject is endowed with new vigor by chaos theory. Cryptography protects the security of today's ubiquitous Internet communication, which as an open network is vulnerable to attack. In this paper, chaos-based cryptography is surveyed with focus on designing chaotic pseudo-random number generators (CPRNGs) for stream cipher and their chip implementation. The properties of the proposed CPRNG are analyzed.